2010
DOI: 10.1902/jop.2010.100053
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fibronectin With Hypogalactosylated Immunoglobulin G in Gingival Crevicular Fluid in Periodontitis

Abstract: IgG and the FN fragment of 48 to 53 kDa in GCF of periodontitis patients and periodontally healthy subjects are physically connected. This fragment was linked to the heavy chains of IgG and the reaction seemed to be particularly intensive with IgG from advanced periodontitis, which contained significantly less galactose in its sugar chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Although complement activation has been described as an important mechanism in tissue damage in periodontal and periimplant disease (209,210), the most accepted interpretation of its activation is the capacity of the periodontopathogens that use it as a mechanism for tissue degradation in favor of the release of nutritional components, and thus the maintenance of biofilms (211,212) and not directly as a mechanism of tissue damage.…”
Section: Relevance Of Auto-antibodies In the Autoimmune Damagementioning
confidence: 99%
“…Although complement activation has been described as an important mechanism in tissue damage in periodontal and periimplant disease (209,210), the most accepted interpretation of its activation is the capacity of the periodontopathogens that use it as a mechanism for tissue degradation in favor of the release of nutritional components, and thus the maintenance of biofilms (211,212) and not directly as a mechanism of tissue damage.…”
Section: Relevance Of Auto-antibodies In the Autoimmune Damagementioning
confidence: 99%
“…1). This might be attributable to a shift toward hypogalactosylated glycoforms occurring during the process of inflammation of the gingiva or significantly less galactose in its sugar chains with immunoglobulin G from advanced CP 50,51 . These findings suggest that inflammation may play a more important role in periodontal tissues than diabetic status.…”
Section: Discussionmentioning
confidence: 89%
“…This might be attributable to a shift toward hypogalactosylated glycoforms occurring during the process of inflammation of the gingiva or significantly less galactose in its sugar chains with immunoglobulin G from advanced CP. 50,51 These findings suggest that inflammation may play a more important role in periodontal tissues than diabetic status. Interestingly, a recent review of the cytokine profiles in the GCF of patients with CP presenting type 2 DM demonstrated that the GCF cytokine profile in patients with and without DM seems to be governed by the intensity of periodontal inflammation, and the role of DM in this regard is rather secondary.…”
Section: Discussionmentioning
confidence: 94%
“…The relative content of immunoglobulin classes (i.e., immunoglobulin index) for every individual CIC was assessed by dot blot protocols from our previous papers [ 47 , 48 , 49 ]. The CIC IgA, IgG, and IgM levels were determined using peroxidase-conjugated goat anti-human IgA, IgG, and IgM antibodies (Boster Biological Technology Co., Ltd., Pleasanton, CA, USA).…”
Section: Methodsmentioning
confidence: 99%